Examining Pancasila as the Basis of the State According to the Perspective of the Islamic Law - Sutrisno, Wiriadi; Iramdan, Iramdan; Muchtar, Asyari (Journal of Mujaddid Nusantara, 2024)
This research aims to examine Pancasila as the basis of the State according to the perspective of Islamic law in the Unitary Republic of Indonesia (NKRI) by investigating the Five Principles based on the perspective of Islamic law (Sharia). The method used in this study is the library research method. Researchers used books from the library as reference material by reviewing literature that followed the theme and exploring empirical studies from previous research related to understanding Pancasila and Islam properly and correctly. The results of this research explain that the relationship between Pancasila and Islam is a mutually necessary relationship where Islam provides an increase in the nation's morale, and the state with its Pancasila guarantees that religious life can take place safely and peacefully. Thus, Pancasila and Islam have a mutually purposeful relationship in organizing and maintaining the Republic of Indonesia to become a country that collects behavioral policies of its population.